Gestión administrativa y su relación con la calidad de servicio en la empresa transportes Policar Domínguez SAC, Huamachuco 2019 - Narcizo Cisneros, Yasmin Edith (2019)
The purpose of this research was to determine how administrative management is related to the quality of service at the Transportes Policar Domínguez SAC, Huamachuco 2019. The following problem was formulated: What is the relationship between administrative management and the quality of service at the Transport Company Policar Domínguez SAC in the city of Huamachuco? Whose hypothesis was: There is a significant and positive relationship between administrative management and service quality in the company Transportes Policar Domínguez SAC, Huamachuco 2019. The research methodology was developed according to the applied type of correlational descriptive level with a non-experimental cross-sectional design. The study population consisted of 50 clients, to whom the survey technique was applied and the chosen instrument was the questionnaire of 10 items for the first variable and 8 items for the second variable. The following results were obtained: 14.00% of the clients indicated that the administrative management is good, 74.00% indicated that it is regular and 12.00% indicated that it is bad. 26.00% of customers indicated that the level of service quality of the company is good, 40.00% indicated that it is regular and 34.00% indicated that it is bad. According to the value of the Spearman Rho coefficient equal to 0.687 and the value of significance less than 0.05, it is concluded: That there is a direct and significant relationship between administrative management and service quality in the company Transportes Policar Domínguez SAC, Huamachuco 2019.